First hand experiences and interactive learning - environmental education and outdoor education in Finland - Jeronen, Eila; Kaikkonen, Marjatta; Smeds, Pia (si, 2010)
The purpose of this article is to be an introduction of outdoor education in Finland. Firstly, Environmental Education theories and models used as background for outdoor education will be presented. Thereafter, a case study, showing how different emotions are correlating with learning and with learning in a different learning environment, will be shortly described. This research is part of project SEED 2009-2011, Sustainable food education for self-efficacy development and it is partly funded by Academy of Finland. At the end of the article, it will be described how environmental education and outdoor education have been taken into account in the Finnish national and local school curricula and given some examples about them in Finnish schools. The article will provide new aspects for teacher education and the development of school curricula
Keywords: Ma; Suomi; ympäristökasvatus; kasvatus; opetus; Finland; environmental education; emotions and learning